Pelatihan Penyusunan Perangkat Pembelajaran Berbasis Lingkungan Hidup di SMPN 25 Kota Malang - Daroe Iswatiningsih; Fida Pangesti; Lila Puspitasari; Dluhayati Dluhayati (Jurnal SOLMA, 2022)
In order to achieve the status of Adiwiyata Mandiri School, SMPN 25 Malang City implements an environment-based curriculum. This has not been balanced with the competence of teachers in the preparation of environmental-based learning tools. The purpose of this service activity is to increase the knowledge and skills of teachers in designing environmentally friendly learning and compiling environmental-based learning tools. This activity was carried out at SMPN 25 Malang City with a total of 11 teachers from 11 fields of study. The method applied is workshops and mentoring which is carried out online and offline. To measure the success of the activity, pretest-posttest, observations, and interviews were conducted in guided discussions. The results of the training activities showed that (1) there was an increase in teacher understanding in designing environmentally friendly learning and (2) an increase in teacher skills in preparing environmental-based learning tools. The training activities for preparing environment-based RPP have increased the knowledge and skills of teachers in preparing environment-based RPP, so that they can support schools in achieving the status of Adiwiyata Mandiri Schools.